Konsumsi fast food dan soft drink sebagai faktor risiko obesitas pada remaja - Ayu Rafiony; Martalena Br Purba; I Dewa Putu Pramantara (Jurnal Gizi Klinik Indonesia, 2015)
Background: Recently, obesity has become health problem which was frequently associated with an increased occurrence of non-communicable diseases. The prevalence of obesity has been increasing in both developed and developing countries. The increasing prevalence of obesity was marked by a shift in eating pattern composition containing high fat, cholesterol, but low in fiber such as consumption of fast food and soft drinks. The imbalance of nutrient intake was one of the risk factors for the emergence of obesity in adolescents. Obesity in adolescents at risk of becoming obese in adulthood and potentially can lead to cardiovascular and metabolic diseasesObjective: This study aimed to find out the prevalence of obesity and to investigate risk factors for energy intake and frequency of consumption of fast food and soft drinks on the incidence of obesity in high school students in Pontianak.Method: This research was an observational study which involves case-control design. The samples in this study are 160 students consisting of 80 obese high school teenagers and 80 non-obese high school teenagers. The choice for a subject of research used proportional stratified random sampling. Measurement of obesity status subject was taken by the measurement of weight and height based on the reference standard WHO / NCHS. It also involves data intake of fast food and soft drinks based on interviews with SQFFQ. Data were analyzed by chi-square test, t-test, and logistic regression.Results: The prevalence of obesity in high school teenagers in Pontianak was 9.29%. The bivariate test result showed no association  between total  energy intake of fast food and obesity (p<0.05; OR=2.27; 95% CI: 1.12-4.64). The relationship between the consumption of modern energy intake of fast food, fast food and soft drink with the local obesity was not statistically significant (p>0.05). There was a relationship between the frequency of total  fast food and of the local fast food consumption with obesity (p<0.05; OR=2.03; 95% CI: 1.03-4.00), (p<0.05; OR=2.63; 95% CI: 1.33-5.25). The relationship between the frequency of fast food consumption in total modern fast food and soft drinks and obesity was not statistically significant (p>0.05). Multivariable analysis showed that the total energy intake was the most dominant factor to the onset of obesity (p<0.05; OR=5.27; 95% CI: 1.64-16.97).Conclusion: Consumption of fast food was a risk factor for obesity in high school teenagers in Pontianak. On the other hand,  soft drink consumption did not become the risk factor for obesity in teens high school in Pontianak.